Codex of Justinian : a new annotated translation, with parallel Latin and Greek text based on a translation by Justice Fred H. Blume - Frier,Bruce,W,Ed
"The Codex of Justinian is, together with the Digest, the core of the great Byzantine compilation of Roman law called the Corpus Iuris Civilis. The Codex gathers legal proclamations issued by Roman Emperors from the second to the sixth centuries C.E. Its influence on subsequent legal development in the Medieval and Early Modern world has been almost incalculable. But the Codex has not, until now, been credibly translated into English. This translation, with a facing Latin and Greek text (from Paul Kruger's ninth edition of the Codex), is based on one made by Justice Fred Blume in the 1920s, but left unpublished for almost a century. It is accompanied by introductions explaining the background of the translation, a bibliography and glossary, and notes that help in understanding the text. Anyone with an interest in the Codex, whether an interested novice or a professional historian, will find ample assistance here"--